Identifikasi Kasus Kekurangan Gizi pada Anak di Bawah Usia Lima Tahun di Kota Makassar - Pujianti, Kurnia; Arsyad, Dian Sidik; Dwinata, Indra (Kes Mas: Jurnal Fakultas Kesehatan Masyarakat, 2017)
Background: South Sulawesi Province is one of provinces in Indonesia with the highest prevalence of severe malnutrition (6.6%) and the highest prevalence was found in Makassar City (3.66%), especially in Kaluku Bodoa Village (3.23%). The aim of this study is to identify risk factor of severe malnutrition on children under five years old in Kaluku Bodoa Village Makassar. Method: This research used case control study design. Case was a child with weight for age Z-scores <-3SD (severe malnutrition) and control was a child with weight for age Z-scores ≥-3 SD these are from the median of WHO reference. Total sample 135 children with 45 cases and 90 controls were recruited. Data were gathered from face to face interviews with mothers of children. Analyses 2x2 table were conducted in this research that produced odd ratio (OR) with 95% confidence interval. Results: Among the cases, a larger proportion of them was female (57.8%) and their age between 25-36 month (42.2%). After adjusting all confounders, childhood severe malnutrition was significantly associated with low economic status (OR=9.514; CI95%=1.219-74.230), infection diseases (OR=5.744; CI95%=2.615-12.613), preterm delivery (OR=3.613; CI95%=1.452-8.987), low birth weight (OR=2.957; CI95%=1.387-6.302) and exclusive breastfeeding (OR=3.537; CI95%=1.481-8.446). Usage health care facilities (posyandu) were not associated with severe malnutrition. Conclusion: Low economic status, preterm delivery, infection diseases, low birth weight, and exclusive breastfeeding are risk factor toward severe malnutriton of children under five years old in Makassar City. Usage health care facilities was not associated with severe malnutrition of children in Makassar City